2020
DOI: 10.5009/gnl19107
|View full text |Cite|
|
Sign up to set email alerts
|

Unmet Psychosocial Needs of Patients with Newly Diagnosed Ulcerative Colitis: Results from the Nationwide Prospective Cohort Study in Korea

Abstract: Background/Aims: Limited data are available regarding psychosocial distress at the time of diagnosis of ulcerative colitis (UC). We investigated the psychosocial burden and factors related to poor health-related quality of life (HRQL) among patients newly diagnosed with moderate-to-severe UC who were affiliated with the nationwide prospective cohort study. Methods: Within the first 4 weeks of UC diagnosis, all patients were assessed using the Hospital Anxiety and Depression Scale (HADS), Work Productivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
(76 reference statements)
1
14
0
Order By: Relevance
“…The Canadian IBD cohort study suggested that patients had higher lifetime prevalence rates of generalized anxiety disorder (GAD) and major depressive disorder (MDD) than the general population at 13.4% and 27.2% [ 20 ]. This is consistent with similar results which were found in studies initiated in the USA [ 7 ], China [ 21 ], Italy [ 22 ], Ireland [ 23 ], and South Korea [ 24 ]. A systematic review that combined multiple clinical studies showed that IBD had 19.2% and 21.2% anxiety and 21.2% depression, almost twice the rate of the general population, and 66.4% anxious mood and 34.7% depression in IBD patients who were also active.…”
Section: Ibd and Depressionsupporting
confidence: 93%
“…The Canadian IBD cohort study suggested that patients had higher lifetime prevalence rates of generalized anxiety disorder (GAD) and major depressive disorder (MDD) than the general population at 13.4% and 27.2% [ 20 ]. This is consistent with similar results which were found in studies initiated in the USA [ 7 ], China [ 21 ], Italy [ 22 ], Ireland [ 23 ], and South Korea [ 24 ]. A systematic review that combined multiple clinical studies showed that IBD had 19.2% and 21.2% anxiety and 21.2% depression, almost twice the rate of the general population, and 66.4% anxious mood and 34.7% depression in IBD patients who were also active.…”
Section: Ibd and Depressionsupporting
confidence: 93%
“…The inclusion and exclusion criteria have been previously described in details. 8,9 We focused on moderate-to-severe UC patients as mild UC patients have limitations in their accuracy of diagnosis, compliance to treatment, and difficulty in long-term follow-up. Diagnosis of UC was based on a combination of conventional clinical, endoscopic, radiological, and histological criteria; symptoms consistent with UC were required to last for more than 4 weeks for the inclusion in the study, according to international criteria.…”
Section: Methodsmentioning
confidence: 99%
“…In the recent years, patient-reported outcomes (PROs) have been accepted as important endpoints in clinical trials and as treatment targets in real life. Health-related quality of life (HRQoL) is mostly known and used PRO; however, it does not focus on the working life and absenteeism and presenteeism [10].…”
Section: Introductionmentioning
confidence: 99%